Pengaruh Pemberian Beasiswa Terhadap Hasil Belajar Mahasiswa Program Studi PPKnFKIP Universitas Riau - Widya Retno Ningsih; Gimin '; Supentri ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the effect of acceptance of the scholarship on learning outcomes among students who received scholarships in the student environment PPKn FKIP University of Riau. Formulation of the problem in this research is: "Are the scholarships effect on student learning outcomes PPKn FKIP University of Riau?". This study aims to determine the effect of granting scholarships to student learning outcomes PPKn FKIP University of Riau. This research was conducted at the University of Riau Pekanbaru PPKn FKIP in October 2015. This study is a quantitative descriptive population in this study is PPKn FKIP Riau University Students. The study population was 50 students with a total sampling technique. Data collection instruments, namely a questionnaire with a total of 35 statements / questions. Thus, the hypothesis formulated "The existence of a positive influence scholarships to student learning outcomes PPKn FKIP Riau University". This is evidenced by testing the hypothesis between variables X and Y, obtained F count of 2,620, calculated F value is then compared with the value of F table with a confidence level of 95%, a significant level of 5% and df I (n-2) or 50 -2 = 48, then F table is equal to 2.20. Because the F count> F table (2.620> 2.20). So this hypothesis Ho is rejected Ha accepted, meaning that there are significant effect between the influence of scholarships to student learning outcomes PPKn FKIP University of Riau. R Square of 0.57 or 57%. It means that donations significantly influence the awarding of scholarships to the learning outcomes of students is 57%, while 43% (100% - 57%) influenced by other variables that are not included in this study.   Keywords: Scholarship, Learning Outcomes.